A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

anonymous

  • 4 years ago

how did the textbook condense this equation? given: x1 + 2x3 + 4x4 = -8 x2 - 3x3 - x4 = 6 3x1 + 4x2 - 6x3 + 8x4 = 0 -x2 + 3x3 + 4x4 = -12 they condensed it to x1 + 3x3 = 0 x2 - 3x3 = 4 x4 = -2 and stated that x3 is arbitrary

  • This Question is Closed
  1. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Adding 2nd and 4th eqns giv 3x4=-6 x4=-2 Applying the value of x4 in the 1st eqn giv x1 + 2x3=0 Applying the value of x4 in the 2nd eqn giv x2 - 3x3 = 4

  2. anonymous
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    oooan add together equations like tht? thanks

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.